Tingkat Kecemasan Santri MTS Terhadap Adaptasi Lingkungan Baru di Pondok Pesantren - Fadilla Nur Syahrani; Herry Susanto; Indra Tri Astuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examined anxiety levels among new Islamic junior high school (MTs) students during adaptation to a new boarding school environment at Pondok Modern Darul Arqam Patean, Kendal. Using a quantitative descriptive-comparative design, total sampling was applied to 212 respondents who met inclusion criteria. Anxiety was assessed using the validated and reliable Generalized Anxiety Disorder-7 (GAD-7) questionnaire. Descriptive analysis indicated that most students experienced severe anxiety, while moderate anxiety was observed in a smaller proportion and mild anxiety appeared rarely. Inferential analysis employed an Independent t-test to compare anxiety scores by gender and One-Way ANOVA to test differences across regions of origin. Results revealed a statistically significant difference in anxiety between male and female students. Regional origin also showed significant differences, and the Games–Howell post hoc test indicated that students from Kendal had significantly higher anxiety compared to those from Pekalongan, Temanggung, Banjarnegara, and Batang, while differences with students from outside Java were not significant. These findings highlight the importance of demographic-sensitive psychosocial interventions to support adaptation among new boarding school students.